Complete Genome Sequence of Canine Papillomavirus Type 11 - Zhou, Dan (American Society for Microbiology, 2014)
Papillomaviruses with the features of epitheliotropic, nonenveloped, circular, and double-stranded DNA belong to the family Papillomaviridae, which contributes to benign and malignant tumors in humans and animals. We report the whole-genome sequence of canine papillomavirus type 11 found at a pigmented plaque located on the skin of a mixed-breed bloodhound.